Pop culture : the culture of everyday life - Fedorak, Shirley (Toronto, Canada : University of Toronto Press, 2009)
'While usually associated with facets of commercial culture, pop culture can and must be analyzed as an important part of material, economic, and political culture. The author begins by defining popular culture, outlining criticisms, and examining the impact of globalization on pop culture. She then explores mass media and popular culture (soap operas, Egyptian melodramas, Afro-Cuban rap music, and virtual communities), artistic expression and popular culture (graffiti art and body art), and gatherings and popular culture (fast food in Japan, equality in sport, and wedding rituals).'--BOOK JACKET.
Includes bibliographical references (p. 133-150) and index.
Keywords: Popular culture -- Textbooks